BALANCING PARENTAL RIGHTS AND CHILD WELFARE: THE BEST INTERESTS THRESHOLD IN HEALTHCARE DECISIONS IN TEGA ESABUNOR & ANOR v. TUNDE FAWEYA & ORS. IN FOCUS. - Hadiza O. Okunrobo; Olaitan O. Olusegun (ABUAD Law Journal, 2024)
Children have the right like other human beings, to enjoy the best attainable standard of health, which includes access to healthcare services. Yet there is no escaping the reality that because of children’s vulnerability and lack of capacity, parents have the responsibility to act on their behalf and must ensure to make these decisions in the child’s best interest. Hence, a refusal to give consent to lifesaving treatment for the child will not be authorised, even if such refusal is from the parents. In cases of this nature, it has become the norm in most jurisdictions for the State to subrogate parental rights in the best interest of the child, this was the posture of the Supreme Court in the case of Tega Esabunor & Anor v. Dr Tunde Faweya & Ors. [2019] 7 NWLR (Pt. 1671) 316 (SC). The paper through doctrinal analysis, reviews and discusses the best interests threshold as a basis for overriding parental rights in protecting the child’s wellbeing. It highlights the responsibilities of parents vis- a - viz the State in ensuring that the child’s interests are best achieved, irrespective of religious or socio-cultural factors. This notwithstanding, the paper asserts that to effectively apply the principle, there must be a well-established standard of practice that completely overrides parental authority to authorise and pay the medical bills of the child and for further issues that may arise between parents in cases of lack of consensus and proper guidelines for medical practitioners.